Role of Rab13, Protein Kinase A, and Zonula Occludens-1 in Hepatitis E Virus Entry and Cell-to-Cell Spread: Comparative Analysis of Quasi-Enveloped and Non-Enveloped Forms - Shigeo Nagashima; Putu Prathiwi Primadharsini; Masaharu Takahashi; Takashi Nishiyama; Kazumoto Murata; Hiroaki Okamoto (Pathogens)
Hepatitis E virus (HEV) exists in two distinct forms: a non-enveloped form (neHEV), which is present in feces and bile, and a quasi-enveloped form (eHEV), found in circulating blood and culture supernatants. This study aimed to elucidate the roles of Ras-associated binding 13 (Rab13) and protein kinase A (PKA) in the entry mechanisms of both eHEV and neHEV, utilizing small interfering RNA (siRNA) and chemical inhibitors. The results demonstrated that the entry of both viral forms is dependent on Rab13 and PKA. Further investigation into the involvement of tight junction (TJ) proteins revealed that the targeted knockdown of zonula occludens-1 (ZO-1) significantly impaired the entry of both eHEV and neHEV. In addition, in ZO-1 knockout (KO) cells inoculated with either viral form, HEV RNA levels in culture supernatants did not increase, even up to 16 days post-inoculation. Notably, the absence of ZO-1 did not affect the adsorption efficiency of eHEV or neHEV, nor did it influence HEV RNA replication. In cell-to-cell spread assays, ZO-1 KO cells inoculated with eHEV showed a lack of expression of HEV ORF2 and ORF3 proteins. In contrast, neHEV-infected ZO-1 KO cells showed markedly reduced ORF2 and ORF3 protein expression within virus-infected foci, compared to non-targeting knockout (NC KO) cells. These findings underscore the crucial role of ZO-1 in facilitating eHEV entry and mediating the cell-to-cell spread of neHEV in infected cells.